IMPLEMENTASI LAYANAN JAMSOSTEK MOBILE DALAM PENGAJUAN KLAIM JAMINAN HARI TUA BPJS KETENAGAKERJAAN CABANG SUKABUMI - Maharani Aulia Putri; Tuah Nur; Dine Meigawati (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The research was aimed at finding out the implementation of the Jamsostek Mobile (JMO) service at BPJS Ketenagakerjaan Sukabumi Branch. The research method used is qualitative method with a narrative approach. The determination of informants using snowball sampling techniques with data collection techniques through observation, interviews and documentation. This research uses policy implementation theory according to Jones (1996). The results of this study indicate that the implementation of the Jamsostek Mobile service in submitting Old Age Insurance claims at BPJS Employment Sukabumi Branch has gone quite well in terms of the organization. However, the interpretation has not been maximized, because the understanding of implementors is not evenly distributed and socialization activities have not reached the expected target, it can be seen from that there are still many companies and participants who have not been educated. Then in its application has not run optimally, because there are still many people and participants who cannot use the Jamsostek Mobile service independently. BPJS Employment Sukabumi Branch should be able to optimize new ways or methods by packaging more interesting information in the interpretation and application of Jamsostek Mobile services, so that it can be understood by every company, community and participants equally. Keywords: Implementation; Jamsostek Mobile Service; Old Age Insurance; Company; Community; Participant.